The Impact of COVID-19 On Tourism From The Perspective of Consumer Groups - Li, Xiangliang (International Journal of Management and Education in Human Development, 2022)
Since the COVID-19 of COVID-19, the global tourism industry has been forcibly suspended. As a result, the tourism industry has been hit hard, and businesses have had to close stores or shorten business hours to reduce losses. The sharp decline in the number of tourists has led to a total collapse of the tourism economy. This paper investigates the desire to travel, including the reasons for the decrease in desire to travel and the methods of increasing the desire to travel, and conducts a questionnaire survey and analysis. In the end, it was concluded that the decline in the desire to travel was highly correlated with the COVID-19 epidemic and the uneasiness about the epidemic. Therefore, the reason for the decline in the desire to travel is the COVID-19 epidemic. At the same time, there is only a minimal correlation between ways to increase the desire to travel and the slowdown of the epidemic.